When women take over: Physician gender and health care provision - Gerald J. Pruckner; Flora Stiftinger; Katrin Zocher (Johannes Kepler University of Linz, Department of Economics, 2024)
The share of female physicians has risen in OECD countries in recent decades, but we know little about the effects of physician gender. We exploit quasi-random assignment of primary care providers (PCPs) to patients and estimate the causal effect of female PCPs on health care provision. Using Austrian register data and a difference-in-differences strategy, we find that female PCPs generate 14% less revenue than male PCPs. This gap is driven by a 6% reduction in the number of patients and a 6.5% decrease in services per patient. Our findings are not consistent with discrimination; instead, female PCPs work fewer hours.
Keywords: I11; I12; J16; J22; 330; physician gender; primary care; gender medicine